2021
DOI: 10.1002/aur.2558
|View full text |Cite
|
Sign up to set email alerts
|

Association of adverse childhood experiences and precuneus volume with intrusive reexperiencing in autism spectrum disorder

Abstract: Compared to typically developing (TD) children, people with autism spectrum disorder (ASD) have an increased risk of adverse childhood experiences (ACEs). Exposure to ACEs is associated with adult ASD psychological comorbidities, such as posttraumatic stress disorder (PTSD). Occurrence of intrusive event reexperiencing, characteristic of PTSD, often causes social dysfunction in adults with ASD, but its pathological basis is unclear. This study examined brain regions related to the severity of intrusive reexper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The atypical connectivity between precuneus and Broca might provide a possible proof for the dysfunction of language in ASD. Recent studies have also found the abnormality of bilateral precuneus in ASD (Kitamura et al, 2021;Lukito et al, 2020). Similar to the prior research (Lukito et al, 2020), our results also showed the increased FC in left precuneus in ASD.…”
Section: Altered Fc Between Broca Area and The Whole Brain In The Con...supporting
confidence: 92%
“…The atypical connectivity between precuneus and Broca might provide a possible proof for the dysfunction of language in ASD. Recent studies have also found the abnormality of bilateral precuneus in ASD (Kitamura et al, 2021;Lukito et al, 2020). Similar to the prior research (Lukito et al, 2020), our results also showed the increased FC in left precuneus in ASD.…”
Section: Altered Fc Between Broca Area and The Whole Brain In The Con...supporting
confidence: 92%
“…Decreased FC between right precuneus with other brain regions was found in ASD [29,46]. In addition to rs-fMRI evidence, there were structure [47][48][49] and task-fMRI studies [50,51] emphasize the role of right precuneus in ASD. Despite the heterogeneity of DMN in different studies, ndings generally indicated hypoactivation of DMN nodes in ASD [52].…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with behavioral findings, this suggests that it is the changes to inter-region communication with the hippocampus that leads to spatial integration deficits, not necessarily hippocampal volume per se . In addition, spatial processing deficits were associated with abnormal cortical volume in regions implicated in spatial manipulation (larger superior parietal lobule; Gogos et al, 2010 ) and intrusive re-experiencing (smaller precuneus; Kitamura et al, 2021 ). Smaller precuneus volumes have also previously been shown to be associated with reduced spatial aspects of personal memories ( Hebscher et al, 2018 ) and disruption of precuneal activity causes network-wide disruption of the autobiographical recollection network and reduced vividness of retrieved memories ( Hebscher et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%